2014
DOI: 10.3892/or.2014.3642
|View full text |Cite
|
Sign up to set email alerts
|

miR-200a suppresses cell growth and migration by targeting MACC1 and predicts prognosis in hepatocellular carcinoma

Abstract: Abstract. miR-200a suppresses tumor development and progression; however, its role in tumor growth and metastasis of hepatocellular carcinoma (HCC) and the underlying mechanism have not been elucidated. In the present study, we identified that miR-200a was markedly downregulated in HCC and exerted suppressive effects on tumor cell growth and metastasis. We identified that miR-200a suppressed tumor growth and metastasis by directly targeting MACC1. In addition, HCC patients with low miR-200a expression had sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 33 publications
(31 reference statements)
3
26
0
Order By: Relevance
“…Downregulation of miR-200a has been reported in several human cancers, including nasopharyngeal carcinoma [12], meningiomas [25], and breast cancer [26]. Moreover, restoration of miR-200a inhibited cell proliferation, migration, and invasion of hepatocellular carcinoma [13], nasopharyngeal carcinoma [12], prostate cancer [14], and ovarian cancer [15]. Conversely, inhibition of miR-200a promoted cancer cell development [12], suggesting that miR-200a may act as a tumor suppressor in human cancer.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Downregulation of miR-200a has been reported in several human cancers, including nasopharyngeal carcinoma [12], meningiomas [25], and breast cancer [26]. Moreover, restoration of miR-200a inhibited cell proliferation, migration, and invasion of hepatocellular carcinoma [13], nasopharyngeal carcinoma [12], prostate cancer [14], and ovarian cancer [15]. Conversely, inhibition of miR-200a promoted cancer cell development [12], suggesting that miR-200a may act as a tumor suppressor in human cancer.…”
Section: Discussionmentioning
confidence: 94%
“…* Wei Zhang zhangweispace@163.com * Zhendong Yu dongboyaa@163.com miR-200a may function as a tumor suppressor in human cancers [12][13][14][15]. Furthermore, a previous study showed that miR200a was downregulated in clinical RCC specimens compared with normal kidney tissues [16].…”
Section: Introductionmentioning
confidence: 94%
“…We found that MACC1 knockdown up-regulated the protein expression levels of LC3-II and Beclin-1 and down-regulated the protein expression level of p62/SQSTM1. MACC1 acted as a target gene for miRNAs, and it has been reported that the expression of MACC1 was down-regulated by miR-143 inhibited the cell migration and invasion in colorectal cancer (Zhang et al, 2012) and MACC1 was down-regulated by miR-200a inhibited the hepatocellular carcinoma cell proliferation and migration (Feng et al, 2015). In our study, miR-590-3p overexpression decreased the expression of MACC1, in addition, MACC1 was identified as a putative target of miR-590-3p.…”
Section: Discussionmentioning
confidence: 99%
“…miR-200a is able to suppress the epithelial-mesenchymal transition (EMT) process [24], which is a critical step in cancer metastasis initiation. In addition, miR-200a has also been shown to suppress cell proliferation and metastasis in several cancers such as pancreatic cancer [5] and hepatocellular carcinoma [6]. More recently, Wu et al reported that miR-200a suppresses pancreatic cancer cell metastasis via the downregulation of DEK, suggesting that miR-200a may constitute a novel target for pancreatic cancer treatment [7].…”
Section: Introductionmentioning
confidence: 99%